Solid Phase Extraction of Ultra Trace Amounts of Cobalt and Nickel on Octadecyl Bonded Silica Membrane Disk Modified with N,N?-Bis(3,5-di-tert-butylsalicylidene)- 1,2-diaminoethane and Determination by Inductively C - Moghimi, Ali; Javad Poursharifi, Mohammad (Asian Journal of Chemistry, 2010)
A highly sensitive and accurate method for preconcentration and determination of ultra trace amounts of cobalt and nickel ions in water samples is proposed. The preconcentration is achieved using C18-silica extraction disks modified with N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-diaminoethane (H2L1). The retained ions on the prepared solid phase was eluted with 10 mL of nitric acid (0.01 M) and measured by inductively coupled plasma-optical emission spectrometry (ICP-OES). The influence of the type and amount of eluent used, pH, sample and eluent flow rates, amount of H2L1 and the effect of other ions on extraction efficiency were investigated. The limits of detection of the method were 0.2 and 0.09 μg L-1 for cobalt and nickel, respectively and provide an enrichment factor of 100. The results obtained on 10 successive extractions and elution cycles revealed relative standard deviations of 1.9 and 1.8 % for cobalt and nickel, respectively. The proposed method has been applied to the determination of ultra trace amounts of cobalt and nickel ions in natural and synthetic water samples with satisfactory results.